Epigenetic analysis of HIV-1 proviral genomes from infected individuals: predominance of unmethylated CpG's - Weber, Stefanie; Weiser, Barbara; Kemal, Kimdar S.; Burger, Harold; Ramirez, Christina M.; Korn, Klaus; Anastos, Kathryn; Kaul, Rupert; Kovacs, Colin; Dörfler, Walter (Virology, 2014)
Efforts to cure HIV-1 infections aim at eliminating proviral DNA. Integrated DNA from various viruses often becomes methylated de novo and transcriptionally inactivated. We therefore investigated CpG methylation profiles of 55 of 94 CpG's (58.5%) in HIV-1 proviral genomes including ten CpG's in each LTR and additional CpG's in portions of gag, env, nef, rev, and tat genes. We analyzed 33 DNA samples from PBMC's of 23 subjects representing a broad spectrum of HIV-1 disease. In 22 of 23 HIV-1-infected individuals, there were only unmethylated CpG's regardless of infection status. In one long term nonprogressor, however, methylation of proviral DNA varied between 0 and 75% over an 11-year period although the CD4+ counts remained stable. Hence levels of proviral DNA methylation can fluctuate. The preponderance of unmethylated CpG's suggests that proviral methylation is not a major factor in regulating HIV-1 proviral activity in PBMC's. Unmethylated CpG's may play a role in HIV-1 immunopathogenesis.
EVALuna2:8239